La cuestión de la dominación: dimensiones de su tratamiento en escritos de Augusto Salazar Bondy - Arpini, Adriana María (2025)
In his writings, Augusto Salazar Bondy addresses the issue of domination on different occasions and in relation to specific problems. We can characterize some of these approaches: As a structural problem of Peruvian and Latin American life (underdevelopment, dependency and domination); as a problem of the situation and condition of our culture, including philosophical work (culture of domination, philosophy of domination); as an axiological problem whose overcoming contributes to a radical transformation of education (domination, values and education); as an anthropological problem, with special reference to the situation of women (gender problem) and to the reformulation of a Latin American humanism (Indian dialogues and anthropology of domination). Salazar Bondy’s analyses anticipate many modern discussions on these issues, providing valuable insights and frameworks for addressing domination in contemporary contexts. His work offers fertile ground for further exploration and adaptation to today’s challenges.